Синфітоіндикаційна характеристика чагарникової рослинності класу Phamno-Prunetea Rivas Godday et Carb. 1961 України - Фіцайло, Т.В. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
На основе метода синфитоиндикации дана экологическая характеристика местообитаний кустарниковых сообществ союзов Pruno - Rubion fruticosi, Berberidion vulgaris, Prunion spinosae, Prunion fruticosae и Lamio purpureae - Acerion tatarici по влажности почвы, содержанию минерального азота и карбонатов в почве, кислотности, солевому режиму (трофности) почвы, терморежиму, континентальности, морозности климата. This paper deals with an ecological evaluation of shrub communities habitats by the method of synphytoindication. Analysed communities belong to Pruno-Rubion fruticosi, Berberidion vulgaris, Prunion spinosae, Prunion fruticosae and Lamio purpureae-Acerion tatarici alliances. Such ecological factors as soil humidity, acidity, mineral nitrogen and carbonates contents in soil, general mineral condition, termoregime, continentality and frosen regime are estimated.